Surgical Medical Nursing Care in Hypertensive Patients with the Application of Benson Relaxation Therapy to Lower Pain Levels in the Nerve Room Rsud Jendral Ahmad Yani Metro City - Lutfi, Miftachur Rohman; Wardoyo, Eko; Susanto, Giri (INDOGENIUS, 2025)
Background & Objective: The purpose of this study was to determine surgical medical nursing care in hypertensive patients with the application of benson relaxation therapy to reduce the level of nyri in the Nerve Room of Rsud Jendral Ahmad Yani Metro City. Method: The method in this scientific work with a descriptive approach to nursing care involving 2 decubitus patients, the instruments used are assessment sheets, head to toe¸ and pain measurement sheets, the application of acute pain treatment using benson relaxation therapy is carried out for 3 days, with the intensity of administration twice a day for 15 minutes. Result: The results of this study found that the main problem that arose in the patient was acute pain, the intervention was arranged by performing benson relaxation therapy, the implementation was carried out for 3 days in the patient, the evaluation of acute pain nursing began to improve on day 3 where when assessing pain obtained a value of 4 and the last day became 2. Recommendations that the author can give are by applying benson relaxation can reduce pain in hypertensive patients and can be done anywhere and anytime without contra indications. Conclusion: Benson relaxation therapy can reduce the pain scale in patients suffering from hypertension.